The Intersex Enchiridion: Naming and Knowledge - Holmes, Morgan (Somatechnics, 2011)
The 2006 Lawson Wilkins Pediatric Endocrinology Society (LWPES) consensus to alter clinical language from ‘intersex’ to Disorders of Sex Development (DSD) has not met its stated objective of destigmatizing the ‘intersex’ label. Rather, DSD works to paper over a problematic understanding of morphological variation as disease. This article interrogates the development of DSD terminology in the clinical context of treating intersex and argues that ‘DSD’ reinstitutionalises clinical power to delineate and silence those marked by the diagnosis; that this silencing is precisely the point of the new terminology; and that it is against that retrenchant impulse that we must protect the viability of ‘intersex’ by continuing its critical deployment. This paper is based on an application of embodiment studies models of critique, combined with an orientation grounded in queer theory to critically interrogate the development of both DSD language and of the ‘new’ guidelines for clinical use, and of the Handbook for Parents that were developed out of the 2006 LWPES meetings. Some of my critique is based on work done over an 18-year period with adults who created the contemporary intersex movement, and on my previous research (in particular: Holmes 2002, 2008, 2010). The point of the argument is not to determine which diagnostic language is superior, but to retain the hard-won right to secure for ourselves the ability to operate socially without the stamp of ‘disorder’ or ‘disease’ strictly delineating what counts as ‘truth’ with regard to embodiment. In this sense, the argument applies to and is drawn out of a larger disability scholarship and activism framework that refuses to permit medicine the final voice in defining our bodies and our selves. The title refers to an older handbook, the enchiridion as a gesture toward the need to retain fundamental knowledge of self that intersexed persons can trace back to a more flexible understanding of embodied differences than the language of disorder asserts in the new Handbook for Parents.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amérique du nord; amériques; approches et analyses; corps; cours; discipline; identité; intersexuation; militance; personnes intersexes; premier cycle; périodes historiques; queer; régions géographiques; santé; sciences humaines; soc2014; sociologie; thématiques; violences; violences médicales; états-unis

Critical intersex - Holmes, Morgan (Ashgate, 2009)
To date, intersex studies has not received the scholarly attention it deserves as research in this area has been centred around certain key questions, scholars and geographical regions. Exploring previously neglected territories, this book broadens the scope of intersex studies, whilst adopting perspectives that turn the gaze of the liberal, humanist, scientific outlook upon itself, in order to reconfigure debates about rights, autonomy and subjectivity, and challenges the accepted paradigms of intersex identity politics. Presenting the latest theoretical and empirical research from an international group of experts, this is a truly interdisciplinary volume containing critical approaches from both the humanities and social sciences. With its contributions to sociology, anthropology, medicine, law, history, cultural studies, psychology and psychoanalysis, Critical Intersex will appeal to scholars and clinical practitioners alike.
Section: 1 vol. (XIV-257 p.) ; 24 cm.
Keywords: LGBTQIA2+; approches et analyses; corps; cours; discipline; intersexuation; inégalités; premier cycle; queer; santé; sciences humaines; sexologie; soc2014; système médical; systèmes d'oppressions; thématiques; violences; violences médicales; études intersexes

Intersex: a perilous difference - Holmes, Morgan (Susquehanna University Press, 2008)
As threatening evidence that sex is not the natural basis upon which oppositional gender roles are built, the intersexed are made to disappear into normative categories, thus aligning once again the rightful place of male and female as opposites.
Keywords: LGBTQIA2+; approches et analyses; corps; cours; discipline; intersexuation; patriarcat; personnes intersexes; premier cycle; santé; sciences humaines; soc2014; sociologie; système médical; systèmes d'oppressions; thématiques; violences; violences médicales